Cost modelling rehabilitation in the home for reconditioning in the Australian context - Roslyn G. Poulos; Andrew M. D. Cole; Dan R. Hilvert; Kerry N. Warner; Steven G. Faux; Tuan-Anh Nguyen; Friedbert Kohler; Fey-Ching Un; Tara Alexander; Jacquelin T. Capell; Claire M. C. O’Connor; Christopher J. Poulos (BMC Health Services Research, 2024)
Abstract Background Inpatient rehabilitation services are challenged by increasing demand. Where appropriate, a shift in service models towards more community-oriented approaches may improve efficiency. We aimed to estimate the hypothetical cost of delivering a consensus-based rehabilitation in the home (RITH) model as hospital substitution for patients requiring reconditioning following medical illness, surgery or treatment for cancer, compared to the cost of inpatient rehabilitation. Methods Data were drawn from the following sources: the results of a Delphi survey with health professionals working in the field of rehabilitation in Australia; publicly available data and reports; and the expert opinion of the project team. Delphi survey data were analysed descriptively. The costing model was developed using assumptions based on the sources described above and was restricted to the Australian National Subacute and Non-Acute Patient Classification (AN-SNAP) classes 4AR1 to 4AR4, which comprise around 73% of all reconditioning episodes in Australia. RITH cost modelling estimates were compared to the known cost of inpatient rehabilitation. Where weighted averages are provided, these were determined based on the modelled number of inpatient reconditioning episodes per annum that might be substitutable by RITH. Results The cost modelling estimated the weighted average cost of a RITH reconditioning episode (which mirrors an inpatient reconditioning episode in intensity and duration) for AN-SNAP classes 4AR1 to 4AR4, to be A$11,371, which is 28.1% less than the equivalent weighted average public inpatient cost (of A$15,820). This represents hypothetical savings of A$4,449 per RITH reconditioning substituted episode of care. Conclusions The hypothetical cost of a model of RITH which would provide patients with as comprehensive a rehabilitation service as received in inpatient rehabilitation, has been determined. Findings suggest potential cost savings to the public hospital sector. Future research should focus on trials which compare actual clinical and cost outcomes of RITH for patients in the reconditioning impairment category, to inpatient rehabilitation.